A call for action to the biomaterial community to tackle antimicrobial resistance. (21st August 2020) - Hall, Thomas J.; Villapún, Victor M.; Addison, Owen; Webber, Mark A.; Lowther, Morgan; Louth, Sophie E. T.; Mountcastle, Sophie E.; Brunet, Mathieu Y.; Cox, Sophie C.
Abstract : The global surge of antimicrobial resistance (AMR) is a major concern for public health and proving to be a key challenge in modern disease treatment, requiring action plans at all levels. Abstract : The global surge of antimicrobial resistance (AMR) is a major concern for public health and proving to be a key challenge in modern disease treatment, requiring action plans at all levels. Microorganisms regularly and rapidly acquire resistance to antibiotic treatments and new drugs are continuously required. However, the inherent cost and risk to develop such molecules has resulted in a drying of the pipeline with very few compounds currently in development. Over the last two decades, efforts have been made to tackle the main sources of AMR. Nevertheless, these require the involvement of large governmental bodies, further increasing the complexity of the problem. As a group with a long innovation history, the biomaterials community is perfectly situated to push forward novel antimicrobial technologies to combat AMR. Although this involvement has been felt, it is necessary to ensure that the field offers a united front with special focus in areas that will facilitate the development and implementation of such systems. This paper reviews state of the art biomaterials strategies striving to limit AMR. Promising broad-spectrum antimicrobials and device modifications are showcased through two case studies for different applications, namely topical and implantables, demonstrating the potential for a highly efficacious physical and chemical approach. Finally, a critical review on barriers and limitations of these methods has been developed to provide a list of short and long-term focus areas in order to ensure the full potential of the biomaterials community is directed to helping tackle the AMR pandemic.